Cadangan rekabentuk rangkakerja bagi pemilihan kontraktor binaan - Ku Ahmad Ezham, Ku Azril Ridzhie (2005)
The construction industry is one of industry that has been widely develop in all over the world without knows the boundaries. Despite the technological development in information technology, construction industry has been slow in adopting changes in its process. Computer Integrated Construction strives to bridge the gaps of information by integrating the tools and processes within the architecture, engineering and construction industries. Tendering is one of procedure practiced by one organization known as a client to choose a trusted and qualified contractor to implement a desired work. Local authorities are one of the organization that involve in tendering procedure as a client for government project. The selection approach is based on ‘Prosedur Penilaian Tender’ which was enforced and used by Jabatan Kerja Raya (JKR). The first objective of this research is to identify procedures in selection of construction contractors for government project. The second objective is to identify the factors that should be considered in the selection process. Finally, a new framework as a Decision Support System (DSS) for evaluating contractors will be developed based on Analytical Hierarchy methodology. It consists of a database system by using Microsoft Access, Expert Choice software for the final decision and Visual Basic 6.0 for the interface. The research methods used include the knowledge acquisition techniques, data analysis and model development process. The study will focus on six main local authorities in Johore to capture the knowledge from the experts on the selection process. It is believe that the propose framework will provide an even more structured and transparence approach and assist in formulating guidelines for clients in contractor selection for construction projects.